Languages and Compilers for Parallel Computing 35th International Workshop, LCPC 2022, Chicago, IL, USA, October 12-14, 2022, Revised Selected Papers - Mendis, Charith; Rauchwerger, Lawrence (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the thoroughly refereed post-conference proceedings of the 35th International Workshop on Languages and Compilers for Parallel Computing, LCPC 2022, held in Chicago, IL, USA, in October 2022. The 9 revised full papers were carefully reviewed and selected from 12 submissions. The conference covers all aspects of languages, compiler techniques, run-time environments, and compiler-related performance evaluation for parallel and high-performance computing. The scope of the workshop encompasses foundational results, as well as practical experience reports and bold new ideas for future systems.
Keywords: Programming languages (Electronic computers).; Programming Language